2005
DOI: 10.1007/s00232-005-0768-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Iron Transport Activity of Ferroportin 1 in Hereditary Iron Overload

Abstract: To investigate the functional significance of mutations in Ferroportin that cause hereditary iron overload, we directly measured the iron efflux activity of the proteins expressed in Xenopus oocytes. We found that wild type and mutant Ferroportin molecules (A77D, N144H, Q248H and V162Delta) were all expressed at the plasma membrane at similar levels. All mutations caused significant reductions in (59)Fe efflux compared to wild type but all retained some residual transport activity. A77D had the strongest effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…Female mice produce more hepcidin mRNA and have higher iron levels in liver and spleen than male mice [17]; this could also account for sex-associated differences in the function of normal or abnormal ferroportin as an iron exporter. Altogether, the molecular basis by which ferroportin Q248H affects iron metabolism is unclear, expression of Q248H in Xenopus oocytes decreased the efficiency of iron export, but did not alter ferroportin regulation by hepcidin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Female mice produce more hepcidin mRNA and have higher iron levels in liver and spleen than male mice [17]; this could also account for sex-associated differences in the function of normal or abnormal ferroportin as an iron exporter. Altogether, the molecular basis by which ferroportin Q248H affects iron metabolism is unclear, expression of Q248H in Xenopus oocytes decreased the efficiency of iron export, but did not alter ferroportin regulation by hepcidin [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been a source of debate whether haploinsufficiency would explain Fpn disease or whether the disease results from a dominant-negative effect. While studies have supported the view that Fpn is a multimer 9,13,24 and that the mutant allele can affect the behavior of the wild-type allele, other studies have suggested that Fpn is monomeric. 10,12,25 All human Fpn mutations are missense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A common deletion (162delVal), has been found in unrelated families (78,115,116 ). Other sequence variations are private, with the exception of the Q248H substitution, which has been detected in populations of African descent but for which contribution to African iron overload is a matter of debate (117)(118)(119)(120)(121). Recent studies have shown that most SLC40A1 sequence variants are unresponsive to hepcidin-mediated internalization (5,122,123 ).…”
Section: Hemochromatosis Attributable To Tfr2 Deficiencymentioning
confidence: 99%